Entrepreneurship in Singapore and the key success factors for entrepreneurial ventures in the automation industry - Ng, Ee Fong (2015)
Over the past two-and-a-half decade, rapid industrialisation and sound economic development enabled Singapore to establish a niche in the world market as a competitive international centre, especially for high value added industries. The Government's economic strategy for the 1990s places great emphasis on positioning Singapore in the global market by developing advanced, high technology industries, and attracting foreign technology. It identified automation and information technology as two key aspects of this development. our project explores two areas : Entrepreneurship in Singapore and the key success factors that contribute to the success of entrepreneurial firms in the automation industry. Furthermore, we also examine the problems encountered by local firms in the automation industry and highlighted the various assistance schemes and incentives available to them. our respondents replied to questionnaires sent to 150 companies in the automation industry. Our analysis and conclusions are based on their reponses. We hope to present findings that will be relevant and informative to executives and students planning their entrepreneurial ventures in this area.